Effectiveness of psychological and educational interventions for the prevention of depression in the workplace: A systematic review and meta-analysis - Juan Ángel Bellón; Sonia Conejo-Cerón; Cayetana Cortés-Abela; José Miguel Pena-Andreu; Antonio García-Rodríguez; Patricia Moreno-Peral (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: Psychological and educational interventions for the prevention of depression have a small-to-moderate effect. However, little is known about their effectiveness in the workplace. We aimed to evaluate the effectiveness of such interventions through a systematic review and meta-analysis of randomized controlled trials (RCT). METHODS: We searched PubMed, PsycINFO, EMBASE, CENTRAL, CIS-DOC and Open Grey for RCT. Search was supplemented with manual searches of reference lists of relevant meta-analyses and trials. We included RCT that assessed either the incidence of depression or the reduction of depressive symptoms, which excluded participants with baseline depression. Measurements were required to have been made using validated instruments and participants recruited in the workplace. Independent evaluators selected studies, evaluated risk bias (Cochrane Collaboration's tool) and extracted from RCT. The combined OR was estimated using the fixed-effects model. Heterogeneity was measured by I^2 and Cochrane's Q. RESULTS: Of the 1963 abstracts reviewed, 69 were selected for review in fulltext. Only three RCT met our inclusion criteria, representing 1246 workers from three different countries and continents. The combined odds ratio was 0.25 [95% confidence interval (CI) 0.11-0.60, P=0.002]; I^2=0% and Q=0.389 (P=0.823). The risk of bias was low in one RCT and moderate and high in the other two, respectively. CONCLUSION: Psychological or educational interventions in the workplace may prevent depression, although the quality of evidence was low.